An emic-etic-emic research cycle for understanding context in under-researched countries - Galperin, Bella; Punnett, Betty Jane; Lituchy, Terri R. (My University, 2022)
Given the importance of understanding the context of management issues in the world, this article discusses the role of both emic (developing culture-specific concepts) and etic (applying concepts across cultures) research in the international management literature. This paper proposes a more comprehensive mixed methods research cycle that can provide researchers with a deeper understanding of the context in under-researched countries. Using a decolonial lens, this theoretical paper proposes that an emic-etic-emic cycle is the best way to disaggregate contextual issues in organizational research, particularly when dealing with human issues in management. By examining a research project on leadership in Africa and the African diaspora from decolonial perspective, our proposed emic-etic-emic cycle (1) stresses the importance of using an emic approach in addition to the dominant etic approach in cross-cultural management; (2) provides researchers with a deeper understanding of context in under-researched countries; and (3) contributes to decolonial approaches to management, which call for a symmetrical dialogue across borders which decentralizes the dominant Western approach, and provides a deeper understanding of management from an indigenous and local perspective. Contextualizing research using the emic-etic-emic cycle can enhance rigor and relevance of the research.
Cross cultural management
Keywords: Emic; Etic; Multi-method research; International management; Mixed methods; Decolonial approaches; Campus Mexicali